Literature Review: The Relationship Beetween Personal Hygiene and Worms Infection (Soil Transmitted Helminths) in Elementary School-Age Children - Sihura, Paskalia Nike Fortuna; Augustina, Indria; Rahman Jabal, Arif (Jurnal Kedokteran Universitas Palangka Raya, 2022)
Soil Transmitted Helminths (STH) infection is most common in children because they like to play without paying attention to the cleanliness of the playground and their personal hygiene. World Health Organization (WHO) reported around 24% of the world’s population are infected with STH infections worldwide and the prevalence in Indonesia ranging of 2,5-62%. STH is caused by many factors, including personal hygiene, which is handwashing habit, nail hygiene habit, foot-wear wearing habit. The aim of this study is to find out the relationship between personal hygiene with the incidence of helminthiasis in elementary school-age children. This study is a literature review and journals as the samples of this research obtained from Scopus and Google Scholar, found 36 national journals and 5 international journals. There were 38 journals that study the relationship between handwashing habit and STH infection, 27 journals wrote that the they were related, while 11 journals wrote not. There were 31 journals that study the relationship between nail hygiene habits and STH infection, 20 journals wrote that the they were related, while 11 journals wrote not. There were 35 journals that study the relationship between the habit of using footwear and STH infection, 18 journals wrote that the they were related, while 17 journals wrote not. The STH that commonly infect are Ascaris lumbricoides, Trichuris trichiura, and Hookworms. There was a correlation between personal hygiene and the infection of STH among elementary school-age children, and the most common STH that caused infection is Ascaris lumbricoides.